KAJIAN NOVEL AWAL LAYUNYA MAWAR BERDURI KARYA TULUS SETIYADI DALAM PERSPEKTIF PSIKOLOGI SASTRA - Onok Yayang Pamungkas; Baekuniah (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2021)
As one form of attention to literary works (novels), researcher interested in studying / analyzing a novel entitled Awal Layunya Mawar Berduri by Tulus Setiyadi. This study aims to 1) explain and describe the structure of the novel, 2) the inner conflicts of the main female characters, and 3) the value of character education in these. To achieve this goal, researcher analyzed the intrinsic elements of the novel related to the psychology of literature. Literary psychology approach used Sigmund Freud's personality theory, and the value of character education refers to Lifelong Guidelines and Character First. The results of this study are. 1) Awal Layunya Mawar Berduri was a novel that groves forward. The story moved based on the time sequence until the end of a story that in the end was sad ending, which is the death of the character Asih. 2) Representation of literary psychology in the Novel Awal Layunya Mawar Berduri found through the aspects of id, ego and superego. 3) The value of Character Education based on Lifelong Guidelines and character first. The conclusion of this research was that the researcher studied Asih's personal character in the Novel Awal Layunya Mawar Berduri used the psychological psychology approach, so the researcher found the personality of Asih's character that distinguishes it from other figures. Awal Layunya Mawar Berduri became an interesting study material, because this novel explores the lives of Asih characters continuously with a storyline that involves the personalities of all the characters. Of the various types of personalities possessed by each character, causing conflict with the character. The methods used by Asih's characters in resolving various conflicts, there is the value of character education that can be used as an example for the reader of the Novel Awal Layunya Mawar Berduri. An important implication of this research is that literature in a psychological perspective gives rise to the values ??of character education that can guide the reader so they can have an attitude of responsibility, integrity, patience, fortitude, and self-control in living life.